Barriers before Students` Entrepreneurial Intentions and Business Initiatives – Results by Empirical Study of Bulgarian and Polish Students - Hristova, V.; Wołejsza, Р. (Економічний вісник Донбасу, 2020)
This article outlines the most important barriers for Bulgarian and Polish students that abandon or significantly reduce the execution of their entrepreneurial intentions and the start of new businesses. There are significant and diverse barriers in the implementation of entrepreneurial activities, but it is especially important that they are outlined for young people with a desire and intentions for entrepreneurship. Entrepreneurial activities developed by young educated people are very important for the initiating and identifying changes in the economy’s and society’s structures. An increasingly important place in this process is taken by higher education institutions, which with their adequate training can "turn" intentions into real entrepreneurial activities or completely lock people with great potential for entrepreneurship. The aim of this article is to highlight some key barriers preventing students to develop their business intentions and initiatives. They are based on a survey conducted in Bulgaria and Poland among students studying entrepreneurial subjects at the “St. Cyril and St. Methodius” University of Veliko Tarnovo and Maritime University of Szczecin, Poland. On this basis, some conclusions are outlined and recommendations are made to universities in terms of strengthening their role as external motivators for launching various entrepreneurial projects by their students. У статті представлено найбільш важливі перешкоди для болгарських та польських студентів, через які вони відмовляються від своїх підприємницьких намірів або значно скорочують їх реалізацію та відкриття нового бізнесу. Існують значні і різноманітні перешкоди на шляху здійснення підприємницької діяльності, але особливо важливо, щоб вони були позначені для молодих людей з бажанням і намірами до підприємництва. Підприємницька діяльність, що розвивається молодими освіченими людьми, дуже важлива для ініціювання та виявлення змін в структурах економіки і суспільства. Все більш важливе місце в цьому процесі займають вищі навчальні заклади, які при відповідній підготовці можуть «перетворити» наміри в реальну підприємницьку діяльність або повністю заблокувати людей з великим підприємницьким потенціалом. Мета цієї статті – виділити деякі ключові перешкоди, що заважають студентам розвивати свої ділові наміри й ініціативи. Вони засновані на опитуванні, проведеному в Болгарії і Польщі серед студентів, які вивчають підприємницькі дисципліни в університеті «Св. Кирила і Св. Мефодія» у Велико Тирново (Болгарія) і Морському університеті Щецина (Польща). На підставі цього робляться деякі висновки і даються рекомендації університетам з точки зору посилення їх ролі як зовнішніх мотиваторів для запуску студентами різних підприємницьких проєктів. В статье описаны наиболее важные препятствия для болгарских и польских студентов, которые отказываются от своих предпринимательских намерений или значительно сокращают их реализацию и открытие нового бизнеса. Существуют значительные и разнообразные препятствия на пути осуществления предпринимательской деятельности, но особенно важно, чтобы они были обозначены для молодых людей с желанием и намерениями к предпринимательству. Предпринимательская деятельность, развиваемая молодыми образованными людьми, очень важна для инициирования и выявления изменений в структурах экономики и общества. Всё более важное место в этом процессе занимают высшие учебные заведения, которые при соответствующей подготовке могут «превратить» намерения в реальную предпринимательскую деятельность или полностью заблокировать людей с большим предпринимательским потенциалом. Цель этой статьи – выделить некоторые ключевые препятствия, мешающие студентам развивать свои деловые намерения и инициативы. Они основаны на опросе, проведенном в Болгарии и Польше среди студентов, изучающих предпринимательские дисциплины в университете «Св. Кирилла и Св. Мефодия» Велико Тырново (Болгария) и Морском университете Щецина (Польша). На основании этого делаются некоторые выводы и даются рекомендации университетам с точки зрения усиления их роли как внешних мотиваторов для запуска студентами различных предпринимательских проектов.